2020
DOI: 10.1371/journal.pone.0241339
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of gait phase entrainment in healthy subjects during rhythmic electrical stimulation of the medial gastrocnemius

Abstract: Studies have shown that human gait entrains to rhythmic bursts of ankle torque for perturbation intervals both slightly shorter and slightly longer than the natural stride period while walking on a treadmill and during overground walking, with phase alignment such that the torque adds to ankle push-off. This study investigated whether human gait also entrains to align the phase of rhythmic electrical stimulation of the gastrocnemius muscle with the timing of ankle push-off. In addition, this study investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…A similar phenomenon occurs in laboratory experiments where individuals are asked to walk on treadmills actuated with controlled oscillations in mediolateral 2 and vertical directions 3,4 . A recent study demonstrated human entrainment with periodic electrical stimulations of the medial gastrocnemius while walking on a conventional treadmill 5 . Furthermore, during development, infants can learn to entrain their bouncing frequency with the resonance of an elastic harness 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon occurs in laboratory experiments where individuals are asked to walk on treadmills actuated with controlled oscillations in mediolateral 2 and vertical directions 3,4 . A recent study demonstrated human entrainment with periodic electrical stimulations of the medial gastrocnemius while walking on a conventional treadmill 5 . Furthermore, during development, infants can learn to entrain their bouncing frequency with the resonance of an elastic harness 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the ankle generates high positive power during push off, the alignment likely means that individuals chose to leverage positive power from the device, similar to our subjects. A different study found that individuals prefer to align pulses of electrical stimulation to the plantar flexors either just before toe off or in advance of heel strike 6 .…”
Section: Discussionmentioning
confidence: 98%
“…However, some of these studies have shown entrainment to be an uncommon response 3 . In a different experimental paradigm, human entrainment was demonstrated with periodic electrical stimulations of the medial gastrocnemius while walking on a conventional treadmill 6 . Furthermore, infants have shown the ability to learn entrainment of their bouncing frequency with the resonance of an elastic harness 7 .…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note, that because muscle performance and injury propensity is often couched using relative rather than absolute measures of fascicle length (i.e., strain vs. mm), using ML models to track lengths of longer muscles would reduce the bearing of inaccuracies in data extraction. Furthermore, feeding ultrasound images along with data from other sensing modalities (e.g., electromyography [35], tensiometry [36,37]) thru ML schemes could provide improved measurement robustness and /or resolution.…”
Section: Limitations Areas For Improvement and Potential Applicationsmentioning
confidence: 99%